Somatic embryogenesis and optimization of regeneration system from immature embryos in maize inbred lines - Obara, Justus Anyieni; Mulwa, Richard; Oyoo, Maurice; Karwitha, Miriam (Research in Biotechnology, 2022)
Maize production and productivity is on a sharp decline due to abiotic and abiotic stresses, therefore, an efficient regeneration protocol is an important tool that can contribute to maize improvement and gene-function studies to improve food security for the ever-growing population. The objective of this study was to optimize a regeneration system for CML 444 inbred line with CML 442 maize inbred line used as a reference. Callus was generated by incubation of immature embryos in Murashige and Skoog (MS) medium with vitamins supplemented with 0 - 4 g L-1 of 2, 4-D hormones, 900 mg L-1 proline, 250 mg L-1casein hydrolysate and 10 mg L-1 of filter sterilized AgNO3, 30 g L-l of sucrose and 3 g L-1 gelrite. Somatic embryo maturation was achieved by transferring 6-week old callus to MS medium with vitamins prepared as previously in callus induction with 60 g L-1 of sucrose and zero plant growth regulators (PGR). Shoot initiation was conducted in MS medium with vitamins supplemented with BAP, NAA at varied concentrations and a 0 mg L-1 control. Plants at a 3-leaf stage that had not rooted were transferred to MS media with vitamins with IBA at a concentration of 0 - 0.3 mg L–l. The 2, 4-D rates were significantly (p≤0.001) different for callus onset and callus induction. The genotype × rate interaction effects showed that 0 and 2 g L-1 2, 4-D had the lowest and highest mean, respectively in both lines during onset and induction of callus. The lines had significant (p≤0.001) effects on shooting induction, however, their means were not significantly different. Similarly, the means for the hormones were not significantly different for shooting induction. The lines, IBA rate and their interaction were significantly (p≤0.05) different for rooting induction. The means for the lines were significantly different for rooting induction in different IBA rates. Conversely, the mean for the IBA rates was significantly different for rooting induction. This study found that plant growth regulators rates during the callus induction stage play a key role during regeneration. This protocol was a success and could provide a fundamental platform for future transformation in this line.